THE COMPARISON OF USING KEYWORD AND ROOT WORD ANALYSIS METHODS TOWARDS STUDENTSâ VOCABULARY MASTERY - RAHAYU, SETIA (Sriwijaya University Learning and Education International Conference, 2016)
Two methods are used to know the different result of studentsâ vocabulary mastery in this research.Those are keyword method and root word analysis. In this research, the researcher used quasiexperiment design. The research was conducted at the second semester of English Department ofMuhammadiyah University of Metro in academic year 2015/2016. The researcher took all of thestudents of second semester as the sample, 23 as the experiment class 1 and 23 were included asexperimental class 2 which were taken by using disproportionate systematic purposive sampling. Incollecting the data, the researcher used pre-test and post-test. In analyzing the data, the researcher usednon-parametric formula. After analyzing the result of data by using non-parametric formula, theresearcher gets the result of tratio is 5,096 and ttable 2,02 (on criterion 1) and 2,69 (on criterion 2). Itmeans that tratio is bigger than ttable, then the criterion of tratio is Ha is accepted if tratio is bigger than ttable.So, there is the significant difference of learning vocabulary between using keyword method and rootword analysis toward studentsâ vocabulary mastery at the second semester of English Department ofMuhammadiyah University of Metro in academic year 2015/2016 and keyword method is moreeffective than root word analysis toward studentsâ vocabulary mastery. Keyword method can be usedfor increasing the studentsâ vocabulary mastery.